A combined cohort analysis of prenatal exposure to phthalate mixtures and childhood asthma - Adgent, Margaret A. (Environ Int, 2020)
BACKGROUND: Previous studies of prenatal phthalate exposure and childhood asthma are inconsistent. These studies typically model phthalates as individual, rather than co-occurring, exposures. We investigated whether prenatal phthalates are associated with childhood wheeze and asthma using a mixtures approach. METHODS: We studied dyads from two prenatal cohorts in the ECHO-PATHWAYS consortium: CANDLE, recruited 2006–2011 and TIDES, recruited 2011–2013. Parents reported child respiratory outcomes at age 4–6 years: ever asthma, current wheeze (symptoms in past 12 months) and current asthma (two affirmative responses from ever asthma, recent asthma-specific medication use, and/or current wheeze). We quantified 11 phthalate metabolites in third trimester urine and estimated associations with child respiratory outcomes using weighted quantile sum (WQS) logistic regression, using separate models to estimate protective and adverse associations, adjusting for covariates. We examined effect modification by child sex and maternal asthma. RESULTS: Of 1481 women, most identified as White (46.6%) or Black (44.6%); 17% reported an asthma history. Prevalence of ever asthma, current wheeze and current asthma in children was 12.3%, 15.8% and 12.3%, respectively. Overall, there was no adverse association with respiratory outcomes. In sex-stratified analyses, boys’ phthalate index was adversely associated with all outcomes (e.g., boys’ ever asthma: adjusted odds ratio per one quintile increase in WQS phthalate index (AOR): 1.42; 95% confidence interval (CI): 1.08, 1.85, with mono-ethyl phthalate (MEP) weighted highest). Adverse associations were also observed in dyads without maternal asthma history, driven by MEP and mono-butyl phthalate (MBP), but not in those with maternal asthma history. We observed protective associations between the phthalate index and respiratory outcomes in analysis of all participants (e.g., ever asthma: AOR; 95% CI: 0.81; 0.68, 0.96), with di(2-ethylhexyl)phthalate (DEHP) metabolites weighted highest. CONCLUSIONS: Results suggest effect modification by child sex and maternal asthma in associations between prenatal phthalate mixtures and child asthma and wheeze.